Paul and the Mosaic law the Third Durham-Tübingen Research Symposium on Earliest Christianity and Judaism (Durham, September, 1994) - Dunn, James D. G. 1939-2020; Durham Tübingen Research Symposium 1994 Durham (Tübingen Mohr, 1996)
Das Ziel des Symposiums war es, so vollständig wie möglich jene Schlüsselpassagen in den Paulusbriefen zu untersuchen, die sich mit seinem Verständnis vom mosaischen Gesetz befassen oder für seine Einstellung dem mosaischen Gesetz gegenüber von Belang sind. Die Vorträge, die anlässlich des Symposiums gehalten wurden, geben eine repräsentative Auswahl der derzeitigen wissenschaftlichen Meinungen über diese Passagen wieder. DIe Konferenzteilnehmer suchten Gemeinsamkeiten in der Auseinandersetzung mit Exegese und Theologie und wollten andere dazu ermutigen, die Positionen stärker zu berücksichtigen, mit denen sie nicht unbedingt übereinstimmen.InhaltsübersichtJames D. G. Dunn: Introduction - Hermann Lichtenberger: Das Tora-Verständnis im Judentum zur Zeit des Paulus. Eine Skizze – Martin Hengel: Die Stellung des Apostels Paulus zum Gesetz in den unbekannten Jahren zwischen Damaskus und Antiochien – Jan Lambrecht: Paul's Reasoning in Galatians 2:11–21 – Bruce W. Longenecker: Defining the Faithful Character of the Covenant Community. Galatians 2:15–21 and Beyond: A Response to Jan Lambrecht – Graham Stanton: The Law of Moses and the Law of Christ. Galatians 3:1–6:2 – Karl Kertelge: Buchstabe und Geist nach 2 Kor 3 – N. T. Wright: The Law in Romans 2 – Richard B. Hays: Three Dramatic Roles. The Law in Romans 3–4 – Otfried Hofius: Die Adam-Christus-Antithese und das Gesetz. Erwägungen zu Röm 5, 12–21 – Hans Hübner: Zur Hermeneutik von Röm 7 – Stephen Westerholm: Paul and the Law in Romans 9–11 – Heikki Räisänen: Faith, Works and Election in Romans 9. A Response to Stephen Westerholm – Stephen Westerholm: Response to Heikki Räisänen – Peter J. Tomson: Paul's Jewish Background in View of his Law Teaching in 1 Cor 7 – Stephen C. Barton: 'All Things to All People.' Paul and the Law in the Light of 1 Corinthians 9: 19–23 – John M. G. Barclay: 'Do we undermine the Law?' A Study of Romans 14:1–15:6 – James D. G. Dunn: In Search of Common Ground
The authors of the papers presented in this conference volume aim to engage in as complete as possible a study of the key passages in the letters of Paul which deal with or have a bearing on his understanding of and attitude to the Mosaic Law. They draw together a representative sample of the range of current scholarly opinion on these passages. The conference participants searched as far as possible for common ground on a wide range of exegetical and theological disputes and wanted to encourage and help facilitate disputants to take fuller account of the strength of the positions they disagree with.»As this volume illustrates so well, the historical and theological issues surrounding Paul's view of the Law are notoriously complex. But it also demonstrates that the 'assured conclusions' of a previous generation have been destroyed without any new 'scholarly consensus' in sight. In doing so, this volume raises afresh the fundamental question of what, for Paul, the significance of the death and resurrection of the Messiah 'under the Law' actually was for the role of the Law itself, not only in the justification and reconciliation of Jews and Gentile in Christ, but also in their continuing life 'in Christ' as believers. May [...] such a volume [...] lead [...] to a renewed dedication to resolve this all-important issue for the meaning of Paul's thought and for the history of Jewish-Christian dialogue.« Scott Hafemann in Shofar 16 (1998), p. 125.Survey of contentsJames D. G. Dunn: Introduction - Hermann Lichtenberger: Das Tora-Verständnis im Judentum zur Zeit des Paulus. Eine Skizze – Martin Hengel: Die Stellung des Apostels Paulus zum Gesetz in den unbekannten Jahren zwischen Damaskus und Antiochien – Jan Lambrecht: Paul's Reasoning in Galatians 2:11–21 – Bruce W. Longenecker: Defining the Faithful Character of the Covenant Community. Galatians 2:15–21 and Beyond: A Response to Jan Lambrecht – Graham Stanton: The Law of Moses and the Law of Christ. Galatians 3:1–6:2 – Karl Kertelge: Buchstabe und Geist nach 2 Kor 3 – N. T. Wright: The Law in Romans 2 – Richard B. Hays: Three Dramatic Roles. The Law in Romans 3–4 – Otfried Hofius: Die Adam-Christus-Antithese und das Gesetz. Erwägungen zu Röm 5, 12–21 – Hans Hübner: Zur Hermeneutik von Röm 7 – Stephen Westerholm: Paul and the Law in Romans 9–11 – Heikki Räisänen: Faith, Works and Election in Romans 9. A Response to Stephen Westerholm – Stephen Westerholm: Response to Heikki Räisänen – Peter J. Tomson: Paul's Jewish Background in View of his Law Teaching in 1 Cor 7 – Stephen C. Barton: 'All Things to All People.' Paul and the Law in the Light of 1 Corinthians 9: 19–23 – John M. G. Barclay: 'Do we undermine the Law?' A Study of Romans 14:1–15:6 – James D. G. Dunn: In Search of Common Ground
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Wissenschaftliche Untersuchungen zum Neuen Testament; Array; Neues Testament; Antike; Paulus (Apostel); Theologie